A method for starting up a graphitized electrolytic cell at low temperature calcination
By adopting the low-temperature roasting start method on the graphitized electrolytic cell, the problem of leakage of electrolyte at the cathode rod of the electrolytic cell is solved, safe, stable and efficient start of the electrolytic cell is achieved, and the service life of the electrolytic cell is extended.
Patent Information
- Application Number
- CN202411990997.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
After the electrolytic cell is roasted by coke powder, the electrolyte leaks from the cathode steel rod when the electrolyte is poured into the electrolyte is prone to occur, which affects the safety of the system and limits the promotion and application of graphitized electrolytic cell.
The low-temperature baking start method of graphitized electrolytic cell is adopted, including laying a coke powder layer on the cathode, installing an electrolyte block and a clay stone furnace, installing a soft connection and a diverter, controlling the baking temperature and temperature increase gradient, extending the baking time in the temperature range of 300-600℃, and blowing air and cooling the cathode steel rod before starting.
Through the low-temperature roasting start method, the inner lining material of the graphitized electrolytic cell is fully sintered, avoiding leakage at the cathode steel rod, ensuring the safety and stability of the start-up, and extending the service life of the electrolytic cell.
Smart Images

Figure BDA0005223649060000071 
Figure BDA0005223649060000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of roasting and starting of an aluminum electrolytic cell, in particular to a low-temperature roasting and starting method for a graphitized electrolytic cell. Background Art
[0002] Aluminum electrolysis is the process of reducing aluminum oxide to metallic aluminum through electrolysis in a molten electrolyte. The electrolytic cell is the core equipment for aluminum electrolysis production, and its performance directly affects the electrolysis efficiency and product quality. In the startup process of the electrolytic cell, baking is an important step. Its purpose is to heat the inside of the electrolytic cell to a certain temperature and state, ensure the full expansion and combination of the materials inside the electrolytic cell, and create good conditions for the subsequent electrolytic reaction. At present, the commonly used electrolytic cell baking startup method is the coke powder baking startup method. The coke powder baking startup method uses coke powder as a conductive medium. After power is turned on, the electrolytic cell is heated and baked using the resistance heat generated by the coke powder. By controlling the time and gradient during the heating process, the inside of the electrolytic cell reaches an appropriate temperature, thereby ensuring that the lining material of the electrolytic cell is fully sintered into a whole. However, after the electrolytic cell is baked with coke powder and started by filling the electrolyte, it is easy to leak electrolyte at the cathode steel rod, affecting the safety of the system, thereby restraining the comprehensive promotion and application of graphitized electrolytic cells, resulting in the inability to continue the subsequent energy saving and consumption reduction work of the electrolytic cell. Summary of the invention
[0003] The invention provides a low-temperature roasting and starting method for a graphitized electrolytic cell, which can solve the problem that the cathode steel rod of the electrolytic cell is prone to electrolyte leakage after the electrolytic cell is roasted with coke powder and electrolyte is poured in and started.
[0004] This application provides the following technical solutions:
[0005] A method for starting a graphitized electrolytic cell at low temperature by roasting comprises the following steps:
[0006] S1. Laying a coke powder layer on the cathode of the graphitized electrolytic cell. The coke powder layer is formed by mixing calcined coke and graphite fragments. The specific resistance of the coke powder layer is 140-155 μΩ·m.
[0007] S2. Use electrolyte blocks and cryolite to load the furnace; install flexible connections and diverters;
[0008] S3, power on for roasting, the roasting time is more than 110h, when the roasting temperature gradient is lower than 25℃ / 2h within 24h, remove the shunt, and the voltage after removal is lower than 3.5V; when the roasting temperature gradient is lower than 15℃ / 2h within 24-48h, remove the shunt, and the voltage after removal is lower than 3.5V; increase the roasting time in the temperature range of 300~600℃;
[0009] S4. Before starting, the temperature reaches 860-880℃, the cathode steel rod is cooled by blowing air, and the electrolyte is poured in. The difference between the temperature of the poured electrolyte and the roasting temperature is within 50℃.
[0010] Beneficial effects: The graphitized electrolytic cell is roasted with coke powder for more than 110 hours, and the graphitized cathode carbon block in the cell lining and the side lining and cathode carbon block are rammed and sintered to form a whole, reaching the starting temperature range of the electrolytic cell, ensuring that the molten electrolyte added to the cell is conductive and working during startup, and the material is quickly melted to ensure safe and stable startup operations. During the roasting process, the roasting time in the temperature range of 300-600°C is extended, and the heating time in the coking stage of the cement paste in the middle and late stages of roasting is extended, thereby reducing the difference in thermal shrinkage between the graphitized cathode carbon block and the cement paste, reducing the difference in matching linear expansion rates between the graphitized cathode carbon block and the cement paste, and eliminating or reducing the probability of cracks between carbons. At the same time, the resistivity of the coke powder layer is reduced, and the temperature of the shunt is adjusted to achieve the purpose of slow heating in the early stage, and to ensure that the electrolysis temperature is reached, and to ensure the normal operation of the graphitized electrolytic cell.
[0011] The cross-sectional dimensions of the graphitized cathode steel bar are 220mm×180mm. The thermal conductivity of the graphitized cathode at 1000℃ is 50W / (m·K), which is much higher than the thermal conductivity of graphite 15-20W / (m·K). The heat dissipation at the steel bar is significantly increased. When the cathode paste is calcined at a temperature exceeding 500℃, the asphalt in the paste is basically carbonized. In the temperature range of 500-900℃, the cold-rammed paste shrinks as the temperature rises, and the heat dissipation capacity is poor. After cooling the cathode steel bar, during the start-up of aluminum pouring, the monitored temperatures of the side wall, steel bar, and furnace bottom all drop to varying degrees, which can effectively prevent leakage at the cathode steel bar and ensure safe start-up.
[0012] Furthermore, the thickness of the coke powder layer is above 20 mm, and the particle size is 1-4 mm.
[0013] Beneficial effects: The thickness of the coke powder layer is above 20mm, ensuring sufficient initial resistance and uniform heat distribution. The particle size range is between 1-4mm, ensuring its uniformity and stability. Ensure that the coke powder layer is flat and has no obvious gaps to avoid local overheating or uneven heat.
[0014] Furthermore, a layer of calcium fluoride is evenly sprinkled around the artificial legs of the graphitization electrolytic cell.
[0015] Beneficial effects: Calcium fluoride can form a protective layer at the artificial legs to prevent electrolyte leakage, enhance the sealing effect, and extend the life of the electrolytic cell.
[0016] Furthermore, the roasting temperature is divided into three stages: the first stage is 25-300°C, and the roasting temperature rise rate is 15-20°C / h; the second stage is 300-600°C, and the roasting temperature rise rate is 10-15°C / h; the third stage is over 600°C, and the roasting temperature rise rate is 5-8°C / h.
[0017] Beneficial effects: Prolong the heating time of the coking stage of the cement paste in the middle and late stages of roasting, thereby reducing the thermal shrinkage difference between the graphitized cathode carbon block and the cement paste, eliminating or reducing the probability of cracks between carbons, and effectively preventing leakage at the cathode steel rod.
[0018] Furthermore, the cathode steel rod is cooled by blowing compressed air.
[0019] Beneficial effect: Through the compressed air system, high-pressure air is blown directly to the surface of the cathode steel rod outside the electrolytic cell, and the air flow is used to take away the heat to achieve rapid cooling. Combined with the high thermal conductivity of the graphitized cathode carbon block group, it can effectively reduce the temperature of the steel rod in the electrolytic cell and prevent leakage at the cathode steel rod.
[0020] Furthermore, after the charged materials are melted, the carbon slag is salvaged, and the voltage is kept within 6.0V after the extinguishing effect, and the materials are adjusted to maintain the operation without effect, and the effect time shall not exceed 30 minutes.
[0021] Beneficial effects: Avoid voltage fluctuations during the electrolysis process, thereby improving electrolysis efficiency and stability, which can significantly reduce DC power consumption and achieve energy-saving production of aluminum electrolysis.
[0022] Furthermore, molten aluminum was poured in 12 hours after startup, and molten aluminum was poured in again 24 hours later, and the voltage was maintained at 5.2V.
[0023] Beneficial effect: With the pouring of molten aluminum, the 800-900℃ isotherm, which was originally concentrated in the steel bar area, rises, the heat dissipation at the edge of the electrolytic cell increases, and part of the heat at the steel bar is transferred to the side wall, reducing the risk of leakage at the steel bar. DETAILED DESCRIPTION
[0024] The following is further described in detail through specific implementation methods:
[0025] Example 1
[0026] A method for starting a graphitized electrolytic cell at low temperature by roasting comprises the following steps:
[0027] S1. Construction of graphitized electrolytic cell cathode
[0028] The cathode structure of the graphitized electrolytic cell includes a tank shell, an insulation layer, an anti-seepage layer and a graphitized cathode carbon block group layer from bottom to top. The insulation layer is composed of a 10mm brucite composite insulation brick layer, a 60mm hard calcium silicate insulation brick layer, a 60mm high-strength ceramic fiber board layer and a 65mm ceramic vermiculite insulation board layer from bottom to top. The anti-seepage layer is composed of a 2mm steel plate and a 171mm dry anti-seepage material layer from bottom to top. The thickness of the graphitized cathode carbon block group layer is 480mm. The graphitized cathode carbon block group layer includes a plurality of graphitized cathode carbon block groups distributed in parallel, and the periphery of the graphitized cathode carbon block group layer is provided with a cathode paste layer, an anti-seepage casting material layer, a vermiculite insulation brick layer and a hard calcium silicate insulation brick layer from the inside to the outside. The two steel bars of the graphitized cathode carbon block group extend from the two side walls of the tank shell to the outside and are connected to the cathode busbar. The gap between two adjacent graphitized cathode carbon block groups is 30-35 mm. The gap and periphery between the graphitized cathode carbon block groups are provided with cathode paste. Vermiculite insulation bricks are first laid between the steel bars of the two adjacent graphitized cathode carbon block groups and then anti-seepage casting materials are poured. Hard calcium silicate insulation bricks are arranged outside the vermiculite insulation bricks. The upper surface of the anti-seepage casting material around the cathode carbon block is smoothed, and side blocks and special-shaped blocks are arranged above the anti-seepage casting material. The special-shaped blocks are made of carbon materials, and the side blocks are silicon carbonitride bricks or silicon carbonitride composite bricks embedded with ceramic fiber boards. The silicon carbonitride composite bricks embedded with ceramic fiber boards are arranged opposite to the steel bars. The extended section of the steel rod 2 exposed from the cathode carbon block 1 passes through the 80mm cathode paste layer, the 130mm anti-seepage casting material layer, the 65mm vermiculite insulation brick layer, and the 60mm xonotlite insulation brick layer from the inside to the outside. The wrapping layer of the extended section of the steel rod corresponds to the cathode paste layer and the anti-seepage casting material layer, and the material of the wrapping layer is a mixture of water glass and SiC ramming material.
[0029] The graphitized electrolytic cell includes a graphitized cathode carbon block group, an electrolytic cell lining structure and masonry materials. The graphitized cathode carbon block group is formed by assembling the graphitized cathode carbon block and the cathode steel rod by the phosphorus pig iron casting method. The graphitized cathode carbon block group is masonry-made with high-strength ceramic fiberboard and vermiculite insulation bricks with better thermal insulation performance, so that the electrolytic cell can achieve a good thermal balance state. Due to the graphitized carbon block and phosphorus pig iron steel rod casting technology, the conductivity of the cathode carbon block is improved, which can maintain a low cathode voltage drop and a stable magnetic fluid state, greatly improve the economic and technical indicators, and extend the life of the electrolytic cell.
[0030] S2, coke powder layer
[0031] A coke powder layer is laid on the cathode of the graphitized electrolytic cell. The coke powder layer is formed by a mixture of coke powder and graphite fragments. The resistivity of the coke powder layer is 140-155μΩ·m, and the thickness of the coke powder layer is 20mm. It is screened and blended many times to ensure that the particle size is 1mm~4mm. Place the grid parallel to the anodes on both sides, sprinkle the prepared coke powder mixture evenly in the grid, scrape the surface with a wooden board or aluminum board, and lay it with a thickness of 20mm. Take out the grid, and do not lay the coke powder mixture in the middle seam. After the laying work is completed, use a tooth rake to draw a longitudinal groove with a spacing of 5cm on the surface of the coke powder mixture layer along the direction of the cathode steel rod, and clean the residual coke powder mixture in the middle seam in time. After passing the inspection, hang the pole to prevent dust and debris from falling on the surface of the coke powder mixture layer.
[0032] S3, hanging pole
[0033] Selection and requirements of anode group: the two anode bottoms are on the same horizontal plane, flat and uniform without pits, cracks or bulges, and the anode guide rod is perpendicular to the anode bottom; the two carbon blocks of each anode group are of the same height when observed with the naked eye; the explosion welding and non-ferrous welding seams of the anode guide rod are full and free of cracks; the phosphorus pig iron in the anode carbon bowl is cast evenly and full without any faults; the anode quality meets the appearance acceptance standards for pre-baked anode quality; the coke powder and phosphorus pig iron attached to the anode surface are cleaned, and the anode blocks are hung according to the principle of uniform distribution.
[0034] Use a crane to align the qualified anode group with the middle position of the anode fixture and place it steadily on the coke powder layer by the anode's own weight. The gap between the anode guide rod and the horizontal busbar is 3-5mm. The anode guide rod must not lean against the horizontal hanging plate or the hook base. When installing the anode, reduce the frequency of adjusting the anode as much as possible and try to complete the installation in one go.
[0035] S4. Loading the furnace
[0036] Electrolyte blocks and cryolite are used for cavity furnace loading. Electrolyte blocks are used to build weir walls at the aluminum outlet and flue ends. The masonry position is on the side of the anode, avoiding the middle seam to prevent the electrolyte from blocking the flow of electrolyte when starting. Sprinkle a layer of calcium fluoride evenly on the artificial legs around. Lay 5cm thick electrolyte powder on the middle seam of the cathode to prevent oxidation. Seal the inter-electrode seam with cardboard, lay 3cm thick cryolite on the cardboard, lay thin iron sheet (2000×300×3mm) on the middle seam, and lay 3cm thick cryolite on the iron sheet. Make ventilation holes with insulating paper at the edge corresponding to the middle of the anode group. After the sealing work is ready, first load the electrolyte block into the tank, and then cover the surface of the electrolyte block with cryolite. The height of the cryolite is flush with the bottom edge of the steel claw (NaF is added appropriately according to the molecular ratio after startup). Insert the temperature measuring tube into the surface of the cathode carbon block through the pre-drilled temperature measuring hole. Seal the pipe opening with asbestos rope to prevent cryolite from entering the temperature measuring tube, which will make it impossible to measure after sintering. Cover the tank cover and clean the site.
[0037] S5. Install soft connection and diverter
[0038] Use "C"-shaped clamps and screws to clamp the flexible connector on the horizontal busbar and the anode guide rod respectively. The two crimping surfaces of the flexible connector must be polished in advance. During installation, it must be pressed tightly and the flexible connector must be in an "S" shape to ensure that the flexible connector has room to expand as the anode moves upward during baking.
[0039] Wet start-up is carried out by installing a diverter. The cross-sectional area of each diverter is 30780mm 2 , the diversion rate is 25%. When in use, clamp the two ends of the diverter on the column busbar and the corresponding horizontal busbar with a clamp. Use a crust block to separate each diverter.
[0040] S6. Calcination
[0041] According to the temperature change, the diverter is removed or the insulation material is added to ensure that the temperature gradient is uniform and controllable. The graphitized cathode baking temperature can be divided into three stages. The first stage is 25-300℃, and the baking temperature rise rate is slow, generally 15-20℃ / h; the second stage is 300-600℃, and the baking temperature rise rate is generally 10-15℃ / h; the third stage exceeds 600℃, the baking temperature rise rate of the electrolytic cell is 5-8℃ / h, and the baking time is controlled at 110-114h. The baking time in the temperature range of 300-600℃ is further extended, and the final baking temperature is controlled at 860-880℃. By extending the heating time of the coking stage of the bonding paste, the difference in thermal shrinkage between the graphitized cathode carbon block and the bonding paste is reduced, and the difference in the matching of the linear expansion rate of the graphitized cathode carbon block and the bonding paste is reduced, and the probability of cracks between carbon gaps is eliminated or reduced.
[0042] Time for splitting shunts (adjusted according to roasting temperature, temperature rise gradient, voltage maintenance and actual on-site conditions): When the roasting temperature rise gradient is lower than 25℃ / 2 hours within 24 hours, disassemble the shunt, and the voltage after disassembly shall not be higher than 3.5V. When the roasting temperature rise gradient is lower than 15℃ / 2 hours within 24-48 hours, disassemble the shunt, and the voltage after disassembly shall not be higher than 3.5V. The third splitting of the shunts shall be determined according to the temperature rise situation, and the 3rd and 4th groups of shunts shall be disassembled, and the voltage after disassembly shall not be higher than 3.5V. The increase in the cell voltage during disassembly shall not exceed 350mV. If the voltage rises sharply (higher than 350mV), the disassembly shall be stopped (the disassembled shunt can be restored if necessary), and the anode current distribution shall be measured. If there is any abnormality, it shall be adjusted in time, and the disassembly operation shall be carried out after the voltage is relatively stable.
[0043] S7, Start
[0044] The average temperature before startup reaches 860-880℃, and the difference between the injected electrolyte temperature and the roasting temperature is within 50℃. During the startup of the electrolytic cell, the cathode steel bar is physically cooled by blowing air. During the aluminum filling period, the monitored temperatures of the side walls, steel bars and furnace bottom all drop to varying degrees, and the temperature can be reduced by about 50℃, reducing the safety risk of startup.
[0045] Open the aluminum outlet of the starter slot, clean the material in the middle seam of the aluminum outlet, set up the chute and confirm that the chute is aligned with the aluminum outlet, and start pouring the hot electrolyte prepared in advance. The total amount of electrolyte poured in must be ensured to be more than 16 tons. When the liquid electrolyte at the flue end has been connected and has a certain height, start to lift the anode. After the first package of electrolyte (at least 8 tons) is poured in, the voltage is maintained at 5-6V, and after the second package of electrolyte is poured in, the voltage is maintained at 7-8V. The depth of the anode immersed in the electrolyte must not be less than 3cm. After starting to pour the electrolyte, the pole distance is guaranteed to be about 10cm (the gyroscope reading is 220-250). Under the condition of ensuring the pole distance, the voltage is maintained at 7-8V. After 24 hours, the voltage drops to about 5.2V. The voltage of the first effect is controlled within 25V, and the time is controlled within 30 minutes. After the furnace material is melted, organize personnel to salvage the carbon slag. After the effect is extinguished, the voltage is maintained within 6.0-6.5V, and the material is constantly adjusted to maintain the effect-free operation as much as possible. 30 minutes after the effect is extinguished, add 1 ton of NaF according to the electrolyte temperature. If a long effect is encountered during the start-up of the electrolytic cell, the site should make a judgment based on the effect voltage, effect time, electrolyte level and temperature, total material amount, etc. The measures taken to extinguish the effect include: adding alumina on the ground and unloading alumina from the overhead crane and the tank control machine to make the alumina concentration in the electrolyte reach about 3%, and then perform the extinguishing effect operation and measure the electrolyte level at the same time. If the electrolyte level exceeds 450mm, contact to extract the electrolyte to reduce the electrolyte level.
[0046] S8, Aluminum filling
[0047] After the effect is extinguished, according to the electrolyte temperature, about 8 tons of molten aluminum are poured in 12 hours after startup. As the molten aluminum is poured in, the 800-900℃ isotherm rises, the heat dissipation at the edge of the electrolytic cell increases, and part of the heat at the steel rod is transferred to the side wall, reducing the risk of leakage at the steel rod. After 24 hours, about 8 tons of molten aluminum are poured in again, and the voltage is maintained at 5.2V.
[0048] The shell surface can be blocked only when more than 90% of the shell surface is crusted to prevent the covering material from entering the tank. The incomplete crust is blocked one after another, and the alumina concentration is manually corrected. The auxiliary voltage steadily drops to 4.5 V. After the shell surface is blocked, the heat loss of the electrolytic cell is reduced, and the voltage will drop further. The electrolyte is adjusted to ensure that the voltage drops quickly from 5.2 V to 4.4 V. The district chief controls to ensure that the voltage is in place to reduce the risk of operation.
[0049] During the first 10 days after aluminum filling, the electrolyte samples were analyzed every day to ensure that the molecular ratio remained above 2.85 and the calcium content remained between 4 and 5.5%.
[0050] S9. Post-startup management of electrolyzer
[0051] Molecular ratio management: the numerator should not be lower than 2.80 in the first month after launch, not lower than 2.7 in the second month, and not lower than 2.55 in the third month. The numerator ratio will be reduced from the 80th day after launch, maintained at 2.45-2.55 in the fourth month, and maintained at 2.40-2.48 from the fifth month onwards.
[0052] Aluminum level management: maintain at 21-23cm in the first month, 22-24cm in the second month, 23-25cm in the third month, and 24-26cm in the fourth, fifth, and sixth months.
[0053] Electrolyte level: The electrolyte height should not be less than 30cm 24 hours after aluminum injection, the electrolyte level should not be less than 28cm 48 hours later, not less than 22cm in the first month, not less than 20cm in the second month, and not less than 17cm from the third to the sixth month.
[0054] Electrolyte temperature: The electrolyte temperature should not be lower than 950℃ in the first week after startup, not lower than 940℃ in the first month, not lower than 935℃ in the second month, and maintained at 928-940℃ from the third month.
[0055] Furnace bottom voltage drop: no higher than 170mV in the first month after startup, no higher than 180mV in the second month, and no higher than 200mV for a long time.
[0056] The charging conditions of the 350KA series graphitization electrolytic cells used in Examples 1-4 are shown in Table 1. Under the same other conditions, the relevant data of the graphitization electrolytic cells powered on, calcined and started are shown in Table 2. The main difference between Comparative Example 1 and Example 1 is that the charging materials and calcination temperatures are different.
[0057] Table 1
[0058]
[0059] Table 2
[0060]
[0061] After the electrolytic cells of Examples 1-4 were started and filled with electrolyte, the cell voltage and state were normal, and no electrolyte leakage occurred. However, the average roasting temperature of the 2237# electrolytic cell of Comparative Example 1 was 917°C before startup. After the electrolyte was filled, the cell voltage and state were normal. However, the molten electrolyte leaked out from the bottom of the four cathode steel rod windows one after another, and the leakage points needed to be plugged in the workshop, which seriously affected the production efficiency and increased the production cost.
[0062] Select 2241# and 2206# electrolytic cells for tracking and recording:
[0063] Before the start-up of the 2241# electrolytic cell, the roasting temperature was 872°C, and the electrolyte was poured in, the electrolyte temperature was 942°C, and sodium fluoride was added after the carbon slag was salvaged, and the aluminum liquid was poured in twice. The temperature of the entire cell was monitored in real time during the entire startup process. The side wall temperature did not exceed 400°C, and the steel rod temperature did not exceed 260°C (blowing). The furnace bottom temperature was normal, and there was no electrolyte leakage. Two months after the start-up of the 2241# electrolytic cell, the operating voltage was 3.950V, the electrolyte level was 17cm, the aluminum level was 25.5cm, the cathode voltage drop was 160mV, the side wall temperature was 286°C on average, and the steel rod temperature was 306°C on average. The temperature of the steel plate at the bottom of the furnace was 81°C, and there were no abnormally high temperature points.
[0064] Before starting up the 2206# electrolytic cell, the roasting temperature was 863°C, and the electrolyte was poured in, the electrolyte temperature was 936°C, and after the carbon slag was salvaged, sodium fluoride was added, and aluminum liquid was poured in twice. During the entire startup process, the temperature of the entire cell was monitored in real time. The side wall temperature did not exceed 400°C, and the steel rod temperature did not exceed 270°C (blowing). The furnace bottom temperature was normal, and the entire process was controllable and no electrolyte leakage occurred. After 2 months, the operating voltage of the 2206# electrolytic cell was 3.952V, the electrolyte level was 19cm, the aluminum level was 23.0cm, the cathode voltage drop was 148mV, the side wall temperature was 283°C on average, and the steel rod temperature was 298°C on average. The furnace bottom steel plate temperature was 77°C, and there were no abnormally high temperature points.
[0065] 2241# and 2135# electrolytic cells were selected for comparison. Compared with 2237# cell, the side wall temperature of 2241# cell was 21°C lower, the steel rod temperature was 44°C lower, and the furnace bottom temperature was 2°C lower after the electrolyte was poured into the cell; after the molten aluminum was poured into the cell, the side wall temperature was 22°C lower, the steel rod temperature was 11°C lower, and the furnace bottom temperature was 2°C lower; in the first week of startup, the side wall temperature was 6°C lower, the steel rod temperature was 1°C higher, and the furnace bottom temperature was 7°C lower.
[0066] Compared with 2237# tank, the side wall temperature of 2135# tank was 34℃ lower, the steel rod temperature was 36℃ lower, and the furnace bottom temperature was 2℃ lower after the electrolyte was poured in. After the aluminum liquid was poured in, the side wall temperature was 32℃ lower, the steel rod temperature was 3℃ lower, and the furnace bottom temperature was 3℃ lower; in the first week of startup, the side wall temperature was 5℃ lower, the steel rod temperature was 3℃ higher, and the furnace bottom temperature was 5℃ lower.
[0067] After the cathode steel rod is cooled down, during the start-up of aluminum pouring, the monitored temperatures of the side walls, steel rods and furnace bottom all drop to varying degrees, reducing the startup safety risk.
[0068] The above are only embodiments of the present invention. The invention is not limited to the field involved in this implementation case. The common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for starting up a graphitized electrolytic cell at low temperature roasting, characterized in that: The steps include: S1. Laying a coke powder layer on the cathode of the graphitized electrolytic cell. The coke powder layer is formed by mixing calcined coke and graphite fragments. The specific resistance of the coke powder layer is 140-155 μΩ·m. S2. Use electrolyte blocks and cryolite to load the furnace; install flexible connections and diverters; S3, power on for roasting, the roasting time is more than 110h, when the roasting temperature gradient is lower than 25℃ / 2h within 24h, remove the shunt, and the voltage after removal is lower than 3.5V; when the roasting temperature gradient is lower than 15℃ / 2h within 24-48h, remove the shunt, and the voltage after removal is lower than 3.5V; extend the roasting time in the temperature range of 300-600℃; S4. Before starting, the temperature reaches 860-880℃, the cathode steel rod is cooled by blowing air, and the electrolyte is poured in. The difference between the temperature of the poured electrolyte and the roasting temperature is within 50℃.
2. The method according to claim 1, characterized in that: The thickness of the coke powder layer is above 20 mm, and the particle size is 1-4 mm.
3. The method according to claim 1, characterized in that: A layer of calcium fluoride is evenly spread at the artificial legs around the graphitization electrolytic cell.
4. The method according to claim 1, characterized in that: The roasting temperature is divided into three stages: the first stage is 25-300°C, and the roasting temperature rise rate is 15-20°C / h; the second stage is 300-600°C, and the roasting temperature rise rate is 10-15°C / h; the third stage is over 600°C, and the roasting temperature rise rate is 5-8°C / h.
5. The method according to claim 1, characterized in that: The cathode steel rod is cooled by blowing compressed air.
6. The method according to claim 1, characterized in that: After the charged materials are melted, salvage the carbon slag, keep the voltage within 6.0V after the extinguishing effect, adjust the materials, maintain the operation without effect, and the effect time shall not exceed 30 minutes.
7. The method according to claim 1, characterized in that: 12 hours after startup, pour in molten aluminum, and 24 hours later, pour in the remaining molten aluminum, and keep the voltage at 5.2V.